2005
DOI: 10.1136/jech.2004.025684
|View full text |Cite
|
Sign up to set email alerts
|

Trends in smoking behaviour between 1985 and 2000 in nine European countries by education

Abstract: Objective: To examine whether trends in smoking behaviour in Western Europe between 1985 and 2000 differed by education group. Design: Data of smoking behaviour and education level were obtained from national cross sectional surveys conducted between 1985 and 2000 (a period characterised by intense tobacco control policies) and analysed for countries combined and each country separately. Annual trends in smoking prevalence and the quantity of cigarettes consumed by smokers were summarised for each education le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
250
7
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(301 citation statements)
references
References 17 publications
36
250
7
8
Order By: Relevance
“…Several studies have concluded that improved lifestyle and better treatments resulted in the compression of morbidity in older individuals during the latter part of the twentieth century (Fries 1980;Mor 2005). Furthermore, in Europe the rate of smoking decreased during this period, which affects the frequency and severity of smoking-related diseases (Giskes et al 2005). Earlier research confirms our results of longitudinal trends of better subjective health in the elderly (Ishizaki et al 2009;Thorslund and Parker 2005;Zack et al 2004).…”
Section: Socioeconomic Factors and Social Support Have Been Related Tsupporting
confidence: 80%
“…Several studies have concluded that improved lifestyle and better treatments resulted in the compression of morbidity in older individuals during the latter part of the twentieth century (Fries 1980;Mor 2005). Furthermore, in Europe the rate of smoking decreased during this period, which affects the frequency and severity of smoking-related diseases (Giskes et al 2005). Earlier research confirms our results of longitudinal trends of better subjective health in the elderly (Ishizaki et al 2009;Thorslund and Parker 2005;Zack et al 2004).…”
Section: Socioeconomic Factors and Social Support Have Been Related Tsupporting
confidence: 80%
“…Even though smoking has decreased among all socio-economic groups, some studies have found that differences between groups have remained stable or even increased over time (Escobedo and Peddicord, 1996;Giskes et al, 2005;Peretti-Watel et al, 2009), which suggest that that diffusion has been blocked or delayed. Following this line of thought, Dixon and Banwell argued that the smoking epidemic model should include a fifth stage marked by "sedimentation of smoking in successive low SES cohorts" (Dixon and Banwell, 2009). 3.…”
Section: Diffusion Of Cigarette Smoking Behaviormentioning
confidence: 99%
“…Socio-economic inequalities in health behaviours and health are well established (Lantz et al, 1998;Dalstra et al, 2005;Giskes et al, 2005;Lahelma et al, 2005). Nevertheless, mutual associations between various dimensions of socioeconomic position and healthy food habits are poorly understood.…”
Section: Introductionmentioning
confidence: 99%